Post-operative face-up or face-down positioning after silicone oil tamponade in retinal surgery: results of a retrospective study - Mohammad Idrees Adhi; Mehreen Adhi; Tariq Aldebasi; Mohammed Hazzazi; Mohammed Nabeel Refka; Aamir Omair (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the complications related to silicone oil, and anatomical and functional outcomes in patients nursed in different postoperative positionings after pars plana vitrectomy with silicone oil injection in retinal surgery. Method: The retrospective cohort study was conducted at the Department of Ophthalmology, King AbdulAziz Medical City, Riyadh, Saudi Arabia, and comprised data of patients who underwent pars plana vitrectomy with silicone oil tamponade from January 2016 to October 2022. The patients were divided into two groups depending on how they were nursed in the postoperative period. Group A patients were nursed in postoperative face-down positioning and group B patients were nursed in the face-up position. Complications related to silicone oil tamponade, visual outcomes and anatomical results were compared between the groups. Data was analyzed using SPSS 26. Results: Of the 157, 97(62%) were males and 60(38%) were females. The overall mean age was 53±20 years. Group A had 87(55.4%) patients, while group B had 70(44.6%). There were 185 eyes involved; 104(56.2%) in group A and 81(43.8%) in group B. Overall, mean postoperative follow-up duration was 25±19 months. Migration of silicone oil in the anterior chamber was more common in group A (p=0.470). Pupil block glaucoma was seen in 2(1.9%) eyes in group A only.Silicone oil-related complications, functional outcomes and anatomical outcomes were non-significantly different between the grpups (p>0.05) except a weak significant difference with respect to redetachments after removal of silicone oil (p=0.047). Conclusion: There was no difference seen in terms of complications as well as anatomical and physiological outcomes related to silicone oil tamponade in face-down or face-up postoperative positioning after pars plana vitrectomy with silicone oil tamponade for complicated retinal detachment surgery. Key Words: Silicone oil, Face-down positioning, Macular folds, Epiretinal membranes, Pblock glaucoma, Silicone oil in anterior chamber.